The Impact of Barriers to Trade In Digital Services on Innovation in Manufacturing Firms - Huang, Xiaoge (Transactions on Economics, Business and Management Research, 2024)
Digital trade in services strengthens the flow and sharing of high-end knowledge, technology, talents and other resources among countries and industries, promotes the accelerated optimization and integration of the global industrial chain and innovation chain, and digital trade in services can further activate the innovation factors and release the innovation potential, injecting new momentum for the innovation and development of Chinese enterprises in the context of the new era. Barriers to trade in digital services refer to various policies, regulations or measures against the cross-border flow of digital services, which may restrict the cross-border transactions of digital service providers and limit consumers' access to and use of digital services. The rapid development of the digital economy has led to further expansion of trade in digital services, which are now deeply integrated into the manufacturing sector. At the same time, barriers to trade in digital services are an issue that cannot be ignored. This paper examines the impact of digital service trade barriers on manufacturing firms' innovation based on micro evidence from listed companies in China from 2014-2019, and finds that digital service trade barriers inhibit firms' technological innovation by hindering their digital transformation, lowering the level of firms' information sharing, and preventing firms from engaging in international innovation cooperation.